Ox-LDL induced profound changes of small non-coding RNA in rat endothelial cells - Wang, Yu; Liu, Tianhua; Xiao, Wenying; Bai, Yanyan; Yue, Dandan; Feng, Liuliu (Frontiers in Cardiovascular Medicine, 2023)
Atherosclerosis (AS) is a common cardiovascular disease with a high incidence rate and mortality. Endothelial cell injury and dysfunction are early markers of AS. Oxidative low-density lipoprotein (Ox-LDL) is a key risk factor for the development of AS. Ox-LDL promotes endothelial cell apoptosis and induces inflammation and oxidative stress in endothelial cells. Small noncoding RNAs (sncRNAs) mainly include Piwi-interacting RNAs (piRNAs), small nucleolar RNAs (snoRNAs), small nuclear RNAs (snRNAs), microRNAs (miRNAs) and repeat-associated RNAs. Studies have shown that small noncoding RNAs play an increasingly important role in diseases. We used ox-LDL to treat rat endothelial cells to simulate endothelial cell injury. The expression changes of sncRNA were analyzed by small RNA high-throughput sequencing, and the expression changes of piRNA, snoRNA, snRNA, miRNA and repeat-associated RNA were verified by quantitative polymerase chain reaction (qPCR). Small RNA sequencing showed that 42 piRNAs were upregulated and 38 piRNAs were downregulated in endothelial cells treated with ox-LDL. PiRNA DQ614630 promoted the apoptosis of endothelial cells. The snoRNA analysis results showed that 80 snoRNAs were upregulated and 68 snoRNAs were downregulated in endothelial cells with ox-LDL treatment, and snoRNA ENSRNOT00000079032.1 inhibited the apoptosis of endothelial cells. For snRNA, we found that 20 snRNAs were upregulated and 26 snRNAs were downregulated in endothelial cells with ox-LDL treatment, and snRNA ENSRNOT00000081005.1 increased the apoptosis of endothelial cells. Analysis of miRNAs indicated that 106 miRNAs were upregulated and 91 miRNAs were downregulated in endothelial cells with ox-LDL treatment, and miRNA rno-novel-136-mature promoted the apoptosis of endothelial cells. The repeat RNA analysis results showed that 4 repeat RNAs were upregulated and 6 repeat RNAs were downregulated in endothelial cells treated with ox-LDL. This study first reported the expression changes of sncRNAs in endothelial cells with ox-LDL treatment, which provided new markers for the diagnosis and treatment of endothelial cell injury.